Peculiarities in WC and W2C Eutectic Phases Dissolution in Interfacial Zones of Composites - Sukhova О.V.; Syrovatkо Yu.V. (Physics and Chemistry of Solid State, 2016)
The structural and phase composition of dissolution-and-diffusion interfacial zones at the particle-matrix interfaces of the composites reinforced with W–C particles infiltrated by a molten iron-base binder has been investigated. The peculiarities in the filler’s phases dissolution during infiltration have been explained within the framework of computed model allowing the estimation of an average atom oscillation frequency of the investigated phases.